Investigate the Mortality, Morbidity and Factors Associate in Thalassemia Patients in Faisalabad, Pakistan - Muhammad Noman; Fatima Asif; Fatima Afzal; Tamazar Javed; Shair Muhammad; Abdullah Khalid; Hafiza Sania Younas; Ghulam Hassan Saif; Maheera Khan; Zain Abbass (Indus Journal of Bioscience Research, 2025)
Introduction: Thalassemia represents a genetic blood disorder that people obtain from their parents through hereditary materials since their bodies produce abnormal types of hemoglobin. The red blood cell destruction occurs in high numbers because of this disorder thus producing anemia.It is a prevalent disease, and in our society, its prevalence is 75%, with 35% of cases in females and 40% in males. Most of the cases are of beta thalassemia major. Objective: We are conducting this research so that in the future, we can correlate the disease with comorbidity in order to reduce the prevalence and so to improve treatment. Method: The study design of this research was retrospective cross-sectional study. We made a questionnaire provided to participants for gathering data.This was followed by a peripheral blood smear to assess cell morphology. Iron deficiency tests were then conducted to rule out other causes of anemia. The questionnaire was carefully designed to gather detailed information on patient and family history, lifestyle, awareness levels, and genetic background Patients were monitored through a follow-up process. Result: The study found that 75% of participants were affected by thalassemia, with 40% males and 35% females, and most cases were beta thalassemia major. Blood tests like CBC confirmed genetic anemia, not due to iron deficiency. The majority of participants lacked awareness about the disease and its hereditary nature, highlighting the need for screening and education programs. Conclusion: In this review we will discuss about Investigate the Mortality, Morbidity and factors associate on Thalassemia patients in Faisalabad 2025Pakistan. Its prevalence rate is high about 75% which is 35% females and 40% males related to our research. Future Perspective: This study's findings will inform evidence-based healthcare policies and interventions to reduce mortality and morbidity in thalassemia patients in Faisalabad, Pakistan, ultimately improving patient outcomes and quality of life. The insights gained will also contribute to the development of targeted prevention strategies and optimized management protocols for thalassemia care in resource-constrained settings. Future research can build upon these findings to explore innovative solutions and best practices for thalassemia management in Pakistan.